Strategi Peningkatan Kinerja Badan Amil Zakat Daerah (BAZDA) Kabupaten Nganjuk (Studi Analisis dengan Metode Balanced Scorecard) - Mukhamad Zakariya (JES (Jurnal Ekonomi Syariah), 2016)
To optimize the role of BAZDA, it requires good fund management strategy so as to create public confidence in disbursing the fund to Bazda rather than giving it directly to mustahik. Directly channeling is closer to the consumptive use that it somewhat obscures productive purposes. Author feel interested in doing research related to performance improvement strategy of BAZDA Nganjuk residence to the management of zakat, infaq, and sadaqah with Balanced Scorecard method. This study titled "Strategy for Performance Improvement of BAZDA Nganjuk Residence (Study Analysis of the Balanced Scorecard method) ".  Type of research used in this paper is qualitative, that is research procedure that produces descriptive data in the form of written or spoken words’ people and behaviors that can be observed. The data used in this study can be divided into two. First, the primary data, that is in the form of interviews with a Nganjuk BAZ board, local government and muzakki. Second, Secondary Data, it is obtained through the financial statements of BAZDA Nganjuk and also from the literature books that support theory of research. The result of study shows; (a) on the basis of the financial perspective, there are still some potential areas of real that can not be absorbed optimally; (b) on the basis of business process perspective, realization of consumptive utilization of zakat is greater than the productive empowerment of zakat; (c) on the basis of customer perspective, when the process of zakat socialization is associated with the result of fund raising, and there are still some potency of zakat that is optimally untapped, it still requires an effort to socialize it more proactive; (d) on the basis of growth and learning, for progress institution of BAZDA Nganjuk, it requires reference sources, both internal and external agencies. Internal agency may be the agency's each period of performance report, while the external agency is from muzakki and mustahik. Keywords: Strategy, performance of BAZDA, balanced scorecard method